1982
DOI: 10.1159/000182631
|View full text |Cite
|
Sign up to set email alerts
|

The Nonlinear Tissue-Binding Character of Fluoride Kinetics in Normal and Anephric Subjects

Abstract: A study has been made of the fluoride kinetics in man, with a series of 5 healthy subjects and 4 patients with renal insufficiency. The fluoride metabolism was found to conform to nonlinear tissue-binding kinetics. Reanalysis of findings on the rabbit reported in the literature yielded equivalent results. The tissue-binding constants elicited -probably associated with the fluoride metabolism of bone – presented no differences between healthy subjects and uremics. Uremics had a clearly lower fractional fluoride… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1985
1985
1996
1996

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…This was also confirmed in a recent study by . It was suggested by Kekki et al (1982) that the non-linear component might be associated with the first phase of fluoride uptake in bone, before this is incorporated into mineral, after which any exchange is slow. For six months, Richards et al .…”
mentioning
confidence: 99%
“…This was also confirmed in a recent study by . It was suggested by Kekki et al (1982) that the non-linear component might be associated with the first phase of fluoride uptake in bone, before this is incorporated into mineral, after which any exchange is slow. For six months, Richards et al .…”
mentioning
confidence: 99%
“…It has been suggested that the nonlinear component may be associated with the first phase of fluoride uptake in bone. (23) Our studies indicate that the kinetics of the plasma profile would be critical to the capacity of the bone to accumulate fluoride. Hence, a dosage regimen that produces more sustained and prolonged plasma levels, in contrast to the high plasma peaks usually seen after intake of plain NaF tablets, might result in a higher degree of fluoride uptake in the bone.…”
Section: Discussionmentioning
confidence: 76%